INSIDE AND OUTSIDE THE WALLS: CLOSED RESIDENTIALS AND SOCIO SPATIAL SEGREGATION IN METROPOLITAN CITIES - Milani, Patrcia Helena [UNESP]; Goes, Eda Maria [UNESP] (Univ Federal Ceara, Programa Pos-graduacao & Filosofia, 2015)
the socio-spatial segregation process is analyzed from its objective and subjective dimensions, in which the walls of closed residential both play a role of barrier material, as a symbolic threshold, which influence the daily practices of the residents and the development of spatial subjectivities. The daily life, as a unit of space and time is our analysis of scale, which allows us to grasp the heterogeneity of the space, generating new meanings to practices involving elaborate and contradictory relations between inside and outside, before and after, change and permanence, space and time, seized through narratives of residents, which tends to conform more walls that bridges in relation to the city and public life.
Keywords: Segregation socio; Spatial practices; Closed residential; Non-metropolitan cities